P110 The boy with moyamoya: strokes and a wisp of smoke. (June 2019) - Dyson, C; Flinn, K; O' Mahony, E; Murphy, AM
Abstract : Aims: Moyamoya is a rare progressive occlusive cerebrovascular disease, affecting both children and adults in a bimodal age pattern. The peak incidence in children is 7–10 years old and can present with a variety of clinical scenarios. Our aim is to describe the clinical presentation, management and outcome to date of a now 5 year old boy who was diagnosed with Moya Moya at 22 months of age. Methods: We report the presenting features, examinations findings and results of radiological images and laboratory investigations, treatment and natural history with regard to our now school age patient. Results: A 22 month old boy presented to the ED following a fall to one side and an episode of high pitched crying. He was afebrile with no recent temperatures or illnesses. His history was notable for a previous afebrile seizure at five months of age lasting over one hour, and recent concerns regarding developmental delay. He had previously had a normal MRI and CT brain, and a normal EEG. The seizure was eventually controlled on phenobarbitone, and an urgent CT brain showed frontal lobe ischaemia with chronic infarct in the left parietal lobe. He was transferred to Temple St Hospital and subsequently diagnosed with moyamoya. He attended Great Ormond Street Children's Hospital for several revascularisation surgeries. He was diagnosed with autism and a sensory processing disorder, and is fed via a gastrostomy tube. He is now five years old, and has been seizure free for several years. He is ambulant, with over 100 words and good comprehension. Conclusions: Our case highlights the success of multidisplinary input, sophisticated sub-specialist care, international expertise and devoted parenting in contributing to the quality of life, despite this devastating disease, in our young patient to date.